Palliative medicine and end of life care in surgery. Issue 4 (April 2021) - Mayers, Jamie; England, Ruth
Abstract: Surgeons are privileged to offer treatments that often cure disease. Optimizing comfort for those who cannot be cured is also a core part of every clinician's duty: surveys repeatedly tell us that when death is approaching, people value quality of life above length of survival. Recognizing when someone is dying can be difficult. Tools exist to help; it is worth noting that emergency presentation with life-threatening symptoms can be a marker of poor prognosis. Clear, effective communication is crucial: understanding the patient's perspective and expectations is vital before attempting to offer information that allows future care planning. Judicious use of surgery combined with careful prescribing will optimize comfort, allowing the patient to live as well as possible for as long as possible. Anticipatory prescribing includes opioid, anti-emetic, anti-secretory and sedative medication. Attention should also be given to care of the bereaved. Generalists should understand when to refer to specialist palliative care and remember that reflecting on care when someone has died can be beneficial for professional wellbeing.